PRENATAL MONITORING OF PREGNANCIES COMPLICATED BY DIABETES MELLITUS - Macura, Maja; Dugalic, Stefan; Todorovic, Jovana; Gutic, Bojana; Milincic, Milos; Bozic, Dragana; Stojiljkovic, Milica; Micic, Jelena; Gojnic, Miroslava (Sanamed, 2022)
Preconception and prenatal monitoring evaluate the condition of the mother’s underlying disease and possible complications during pregnancy. Before conception, patients with diabetes should be informed that suboptimal glycoregulation is associated with reduced fertility and pregnancy losses. The task of the perinatologist in pregnancies affected by diabetes mellitus is to prevent complications of the underlying disease, such as hypoglycemic crises. Another important component of prenatal care in diabetic pregnancies is the recognition and prevention of pregnancy complications such as preeclampsia, polyhydramnios, congenital malformations, fetal macrosomia, and infections.